Target enzyme mutations are the molecular basis for resistance towards pharmacological inhibition of nicotinamide phosphoribosyltransferase - Christensen Mette K; Imai Shin-Ichiro; Yoshino Jun; Kiess Wieland; Garten Antje; Petersen Jakob G; Olesen Uffe H; Fristrup Peter; Thougaard Annemette V; Björkling Fredrik; Jensen Peter B; Nielsen Søren J; et al. (BMC Cancer, 2010)
Abstract Background Inhibitors of nicotinamide phosphoribosyltransferase (NAMPT) are promising cancer drugs currently in clinical trials in oncology, including APO866, CHS-828 and the CHS-828 prodrug EB1627/GMX1777, but cancer cell resistance to these drugs has not been studied in detail. Methods Here, we introduce an analogue of CHS-828 called TP201565 with increased potency in cellular assays. Further, we describe and characterize a panel of cell lines with acquired stable resistance towards several NAMPT inhibitors of 18 to 20,000 fold compared to their parental cell lines. Results We find that 4 out of 5 of the resistant sublines display mutations of NAMPT located in the vicinity of the active site or in the dimer interface of NAMPT. Furthermore, we show that these mutations are responsible for the resistance observed. All the resistant cell lines formed xenograft tumours in vivo. Also, we confirm CHS-828 and TP201565 as competitive inhibitors of NAMPT through docking studies and by NAMPT precipitation from cellular lysate by an analogue of TP201565 linked to sepharose. The NAMPT precipitation could be inhibited by addition of APO866. Conclusion We found that CHS-828 and TP201565 are competitive inhibitors of NAMPT and that acquired resistance towards NAMPT inhibitors can be expected primarily to be caused by mutations in NAMPT.